2010
DOI: 10.1108/02683941011035304
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on followers' innovation implementation behavior

Abstract: Purpose -The purpose of this paper is to provide a deeper understanding of how transformational leadership relates to followers' innovation implementation behavior, the psychological mechanisms of this relationship, and the role of individual perceptions of climate for initiative. Design/methodology/approach -Perceptual data were collected from 198 employees in lower and middle management positions of a multinational automotive corporation. Relationships were tested using hierarchical regression analysis. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(57 citation statements)
references
References 75 publications
1
55
1
Order By: Relevance
“…Some previous research has shown the influence of transformational leadership on innovation. Transformational leadership is closely linked to the behaviour of employees in the implementation of innovation [1]. Transformational leaders have a good effect on creativity on employees and the organization [2].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous research has shown the influence of transformational leadership on innovation. Transformational leadership is closely linked to the behaviour of employees in the implementation of innovation [1]. Transformational leaders have a good effect on creativity on employees and the organization [2].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, an emerging body of research highlights the crucial role of direct supervisors in signalling such support as they are expected to respond to and evaluate new ideas and initiatives voiced by individuals (e.g., Eisenbeiss, Van Knippenberg, & Boerner, 2008;Michaelis, Stegmaier, & Sonntag, 2010).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Lambdas (Λ), on the other hand, seek achievement and uniqueness as an ultimate end goal. As a result, they are more likely to interpret products based on their individual responses to the product, how it helps/prevents them to stand out, and how the product benchmarks against their regular consumptive patterns.Furthermore, a distinction is often made between transformational leadership and transactional leadership (Dion, 2008;Fitzgerald & Schutte, 2010;Gong et al, 2009;Michaelis et al, 2010).…”
Section: Police Leadershipmentioning
confidence: 99%